Awareness Raising through Exposure, Inspiration, and Positive Emotion: The Artwork of Svenja Meyer - Monica Farfan; Svenja Meyer (Soil Organisms)
For those of us who study soil organisms and teach about the importance of soil biota and its many ecosystem functions, we often have the privilege of understanding these organisms at a deeper level than the average person through our work. For those who work on the frontiers of education and science communication, we seek ways of helping explain and raise awareness of these often minute and hidden creatures right below our feet.